AR-MUSCLE Mobile Augmented Reality Innovation for Interactive Learning of Musculoskeletal Anatomy and Physiology in Health Science Students - Abiyasa, Maulana Tomy; Syah, Riska Muzakki; Ernawati, Dyah; Utami, Rinta Martha; Mustaqim, Nurudin Wafiq; Ardiansyah, Muhammad Fauzi (VISIKES, 2025)
The implementation of clinical coding for musculoskeletal disorders requires comprehensive knowledge of human anatomy and physiology. The advancement of Augmented Reality (AR) technology provides an effective approach to addressing students’ learning difficulties in health sciences, particularly in understanding the musculoskeletal system. This study aims to develop a mobile-based Augmented Reality application called AR-MUSCLE, designed as an interactive learning medium for health science students. The research background stems from the difficulty students face in mastering complex anatomical and physiological concepts through conventional learning media limited to 2D illustrations and static models. The research employed a Research and Development (R&D) design using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The application integrates interactive 3D visualization of the human musculoskeletal system, structured learning modules, and evaluation quizzes. The development process involved needs analysis, system design using the Unified Modeling Language (UML), 3D model creation, AR system integration via Unity Engine, and prototype evaluation. Functional testing (Black Box Testing), usability testing, and user satisfaction assessments were conducted to ensure reliability and effectiveness. The results showed that all application features functioned properly and responsively as designed. The usability testing yielded a very low error rate (<5%), indicating that users could easily navigate and operate the application. The user satisfaction survey demonstrated very high ratings, averaging above 95% across four dimensions: learnability, responsibility, satisfaction, and accuracy. Nevertheless, improvements are required in the system responsibility aspect since the mobile-based application depends heavily on stable internet connectivity and adequate device specifications to support the interactive 3D rendering process. In conclusion, AR-MUSCLE proves to be an effective Augmented Reality-based interactive learning tool that enhances students’ conceptual understanding, motivation, and engagement in learning musculoskeletal anatomy and physiology. This research contributes to strengthening digital learning innovation in health education and supports the transformation toward technology-integrated teaching and learning models.